Principles of Cloud Computing Capacity Planning - Velev, D.G.; Zlateva, P.V. (Математичне та комп'ютерне моделювання. Серія: Фізико-математичні науки, 2010)
The term «Cloud» is used an abstraction of the Internet infrastructure. The cloud infrastructure provides for a computer infrastructure platform as a service. The cloud computing providers offer online common business applications accessed by Web browsers, and the software and data are stored in servers. One of the most advertised advantages of the cloud-computing paradigm is the reduction of hardware deployment and installation times. Cloud storage and compute instances must be viewed as another type of resource. The promise of cloud computing is that it can increase capacity «on-demand» easily and not necessarily automatically. Since every compute instance is a service, many cloud providers put the control of those instances in the hands of their customers. The decision when to launch new instances and their number can be crucially important regarding the rising traffic and computing capabilities and in those circumstances all could end with inefficiencies in cloud capacity. The current article attempts to propose guidelines for efficient planning of cloud capacity. Термин cloud (облако) использется как абстракция Интернет инфраструктуры. Инфраструктура облака (cloud infrastructure) предоставляет компьютерную инфраструктуру под платформой для виртуализации (virtualization) как сервис (обслуживание). Поставщики облачных вычислительный (cloud computing) предоставляют в онлайн режиме общие бизнес приложения, доступ к которым осуществляется web-браузером, в то время как программное обеспечение и данные сохранены на серверах. Одно из наиболее рекламируемых преимуществ облачных вычислений — сокращение времен развертывания и установки аппаратных средств. Сохранение данных и вычислительные операции в облаке должны быть рассмотрены как другой тип ресурса. Так как каждая вычислительная операция является облачным сервисом, оплачиваемым пользователями, многие поставщики облачных сервисов помещают их контроль в руках своих клиентов. Решение о запуске нового сервиса и их число может быть кардинально важным по отношению наращивания трафика транзакций и вычислительных способностей, что в пиковых ситуациях могли бы закончить неэффективностью в возможностях облака. Настоящая статья пытается предложить набор принципов для эффективного планирования возможности облачных вычислений.